2007
DOI: 10.1038/sj.emboj.7601559
|View full text |Cite
|
Sign up to set email alerts
|

XRCC4:DNA ligase IV can ligate incompatible DNA ends and can ligate across gaps

Abstract: XRCC4 and DNA ligase IV form a complex that is essential for the repair of all double-strand DNA breaks by the nonhomologous DNA end joining pathway in eukaryotes. We find here that human XRCC4:DNA ligase IV can ligate two double-strand DNA ends that have fully incompatible short 3 0 overhang configurations with no potential for base pairing. Moreover, at DNA ends that share 1-4 annealed base pairs, XRCC4:DNA ligase IV can ligate across gaps of 1 nt. Ku can stimulate the joining, but is not essential when ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
134
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(139 citation statements)
references
References 49 publications
5
134
0
Order By: Relevance
“…Although their joining efficiencies differ, defects in KU80 or in XRCC4 both abrogated error-free end-joining. In non-fully complementary ends, wild-type cells primarily use the annealing of two of the 4Pnt, in a process consistent with in vitro biochemical data (25,26). PolX polymerases participate in the synthesis of nucleotide gaps (27,28).…”
Section: Discussionmentioning
confidence: 72%
“…Although their joining efficiencies differ, defects in KU80 or in XRCC4 both abrogated error-free end-joining. In non-fully complementary ends, wild-type cells primarily use the annealing of two of the 4Pnt, in a process consistent with in vitro biochemical data (25,26). PolX polymerases participate in the synthesis of nucleotide gaps (27,28).…”
Section: Discussionmentioning
confidence: 72%
“…These proteins are structurally similar to and interact with the yeast Lif1 and human XRCC4 subunit of the DNA ligase IV complex (20 -23, 25, 28, 30, 35). In addition, XLF enhances joining by DNA ligase IV-XRCC4 of both matched and mismatched DNA ends (31)(32)(33)(34)46). Using a combination of molecular genetic and biochemical approaches, we have demonstrated that Nej1 not only contributes to the final ligation step of NHEJ but also plays a critical role in the initiation of the NHEJ pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Although DSBs are detectable in B cells with AID +/C-termΔ mutations, they are undetectable in UNG- deficient B cells (4,20). Fewer AID-and/or UNG-induced DNA lesions likely leads to staggered and long single-stranded DNA breaks that may require extensive processing by polymerases, such as polymerase μ or ζ (34,35). Polymerase-mediated repair might lead to the insertion of nucleotides at the junctions due to template-independent synthesis, or to microhomologies due to fillin synthesis (34,36).…”
Section: Position Of Sμ and Sα Breakpoints In Switchmentioning
confidence: 99%
“…Fewer AID-and/or UNG-induced DNA lesions likely leads to staggered and long single-stranded DNA breaks that may require extensive processing by polymerases, such as polymerase μ or ζ (34,35). Polymerase-mediated repair might lead to the insertion of nucleotides at the junctions due to template-independent synthesis, or to microhomologies due to fillin synthesis (34,36). The polymerase-mediated repair is likely associated with the components of c-NHEJ (34); however, the microhomology length of >10 nucleotides and the location of the Sμ breakpoints observed in the analyzed patients argues for another pathway involving DNA end-resection to search for donor/acceptor homology.…”
Section: Position Of Sμ and Sα Breakpoints In Switchmentioning
confidence: 99%